A decade of entrepreneurship research: Clustering-based topic evolution and strategic implications - Choi, Daesoo (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates the thematic evolution of entrepreneurship research between 2015 and 2024, focusing on how dominant topics have shifted in response to sustainability imperatives, digital transformation, and crisis-driven resilience. Drawing on 1,876 entrepreneurship-related articles retrieved from the Research Information Sharing Service (RISS), the study employs a clustering-based topic modeling approach using TF–IDF vectorization and K-Means clustering, with temporal comparisons between two phases (2015–2019 and 2020–2024) supported by co-occurrence network analysis. The findings reveal a clear paradigmatic shift: early studies emphasized entrepreneurship education, SME financing, innovation, and regional development, while later research concentrated on digital and platform-based entrepreneurship, sustainable and green entrepreneurship, resilience under crises such as COVID-19, and inclusive entrepreneurial ecosystems. These transitions illustrate the movement from institution- and financing-centered perspectives toward frameworks addressing global challenges such as ESG adoption, climate change, and Industry 4.0. The study concludes that entrepreneurship functions both as a mirror of societal transformations and as a driver of innovation and adaptation. Theoretically, the research underscores the importance of embedding entrepreneurship within temporal and socio-technical contexts. Practically, it offers strategic implications for policymakers, educators, and practitioners, including the promotion of digital and sustainable entrepreneurship, the strengthening of resilience capacities, and the integration of inclusivity into entrepreneurial ecosystems.